An Industrial and Sustainable Platform for the Production of Bioactive Micronized Powders and Extracts Enriched in Polyphenols From Olea europaea L. and Vitis vinifera L. Wastes - Romani, Annalisa; Campo, Margherita; Urciuoli, Silvia; Marrone, Giulia; Noce, Annalisa; Bernini, Roberta (Frontiers in Nutrition, 2020)
In the last few years, literature data has reported that the healthy status is related to the consumption of foods rich in polyphenols, bioactive compounds found in the plant world, in particular in vegetables and fruit. These scientific evidences have led to an increase of the demand of functional foods and drinks enriched in polyphenols, so that plant materials are more and more requested. The availability of food and agricultural waste has negative effects on economy, environment and human health. On the other hand, these materials are a precious source of bioactive compounds as polyphenols. Their recovery and reuse from wastes are according to the circular economy strategy, which has introduced the “zero waste concept”. However, the process is convenient from an economic and environmental point of view only if the final products are standardized and obtained using sustainable and industrial technologies. In this panorama, this paper describes an industrial and sustainable platform for the production of micronized powders and extracts enriched in polyphenols from Olea europaea L. and Vitis vinifera L. wastes useful for food, cosmetics, and pharmaceuticals sectors. The platform is based on drying plant materials, extraction of polyphenols through membrane technologies with water, and when necessary, concentration of the final fractions under vacuum evaporation. All powders and extracts were characterized by HPLC/DAD/MS analysis to define the qualitative and quantitative content of bioactive compounds and insure their standardization and reproducibility. The chromatographic profiles evidenced the presence of secoiridoids, flavonoids, anthocyanins, hydroxycinnamic acids, and condensed tannins, respectively. An overview of the biological activities of the main polyphenols present in Olea europaea L. and Vitis vinifera L. powders and extracts is reported in view of biomedical applications.